STATISTICAL ESTIMATION OF THE READINESS TO THE DIGITAL TRANSFORMATION OF THE ECONOMY OF THE REPUBLIC OF BELARUS - L. I. Karpenko; A. B. Belsky (Цифровая трансформация)
The concept of digital transformation and its difference from informatization processes are considered in the article. The dynamics of the share of the gross added value of the ICT sector in theRepublicofBelarusis analyzed, and this indicator is compared with the OECD countries. A multiplicative index model that allows assessing the influence of the main factors on the dynamics of the share of the ICT sector in the GVA has been developed. A cluster analysis of the types of economic activity on the indicators of the use of ICT was carried out (e-mail, Internet, local area networks), as well as the availability of its own website, as a result of which groups of "digital leaders" and "digital outsiders" were singled out. The estimation of readiness of the economy of theRepublicofBelarusfor digital transformation in 2016 is presented on the basis of the share of economic activities that are "digital leaders" in the total value of GVA.